Bioassessment of Macroinvertebrate Communities Influenced by Gradients of Human Activities - Rui Li; Xianfu Li; Ronglong Yang; Muhammad Farooq; Zhen Tian; Yaning Xu; Nan Shao; Shuoran Liu; Wen Xiao (Insects, 2024)
This study explores the impact of anthropogenic land use changes on the macroinvertebrate community structure in the streams of the Cangshan Mountains. Through field collections of macroinvertebrates, measurement of water environments, and delineation of riparian zone land use in eight streams, we analyzed the relationship between land use types, stream water environments, and macroinvertebrate diversities. The results demonstrate urban land use type and water temperature are the key environmental factors driving the differences in macroinvertebrate communities up-, mid-, and downstream. The disturbed streams had lower aquatic biodiversity than those in their natural state, showing a decrease in disturbance-sensitive aquatic insect taxa and a more similar community structure. In the natural woodland area, species distributions may be constrained by watershed segmentation and present more complex community characteristics.